Type of character and schemes mental problems faced situations in students - UNHEVAL 2014 - Fonseca-Livias, Abner A. (2019)
The purpose of the study was to determine the type of character and mindset facing the problematic situation in students UNHEVAL 2014. The methodology used was the analytical, transversal and prospective; the sample was 112 students; the instruments used were: Primer test the mindset and characterological Berger questionnaire. The results indicated that students with emotional character and mindsets have Ch¡2 valué of 183.98 p 0.219; students active character and mindsets have Chi2 156.68 p valué of 0.76, and students of secondary character and mindsets have Chi2 p valué of 0.827 152 573. In conclusión, mental and schemes charactertypes have no inuence on coping with problems.